Trypanosomatid species infecting bats in the Fiocruz Atlantic Forest Biological Station, an urban forested fragment in Rio de Janeiro, Brazil - Alice Pereira Berbigier; Juliana Helena da Silva Barros; Roberto Leonan Morim Novaes; Ricardo Moratelli; Bruno Alves; Cristiane Varella Lisboa; Ana Maria Jansen; André Luiz Rodrigues Roque (PLoS ONE, 2026)
Trypanosomatids (Protozoa; Kinetoplastea) are obligate parasitic protozoans that infect a wide range of vertebrate hosts, including bats – the only volant mammals, widely distributed across the globe. In Rio de Janeiro, Brazil, Atlantic Forest remnants persist within urban landscapes, including the Fiocruz Atlantic Forest Biological Station (EFMA), a unit embedded in a highly urbanized environment. Between 2013 and 2019 (excluding 2015), field surveys were conducted in four landscape physiognomies with different degrees of environmental degradation. Blood and other tissue samples (spleen, liver and skin) were collected from bats to investigate the infection and diversity of trypanosomatid infections. A total of 270 bats were examined through parasitological techniques (fresh blood examination and hemoculture) and molecular diagnosis through phylogenetic analysis. Overall, 24.1% (n = 65) of bats tested positive for trypanosomatids. Molecular identification revealed a diverse assemblage of species, including Crithidia mellificae , Trypanosoma cruzi (DTUs TcI and TcII), Trypanosoma dionisii , Trypanosoma sp. Neobat 1 and 4, Trypanosoma lainsoni, and Trypanosoma rangeli A. Our findings underscore the critical role of direct molecular detection in tissue samples for uncovering infections missed by traditional parasitological methods, particularly those caused by uncultivable species/genotypes such as Trypanosoma sp. Neobat 1 and 4. The recurrent detection of T. dionisii , T. cruzi DTU TcI and T. rangeli A, reinforces their sustained circulation in bats from this urban-forest interface. Moreover, the presence of C. mellificae , traditionally regarded as a monoxenous species, adds new bat hosts to the already extant list of mammal species recognized as able to harbor this parasite. Notably, this study provided the first record of T. lainsoni and T. cruzi DTU TcI in mammals from the EFMA, highlighting a surprising richness of trypanosomatids in this small, and human-impacted forest remnant. The high diversity of trypanosomatid communities infecting bats, recognized as habitat-resilient hosts, reinforces the complexity of the sylvatic transmission of those parasites that may not be disrupted even under strong anthropogenic pressures.